Occupational stress in mainstream and special needs primary school teachers and its relationship with self-efficacy. Issue 1 (2nd January 2023) - Antoniou, Alexandros-Stamatios; Efthymiou, Vasiliki; Polychroni, Fotini; Kofa, Olga
ABSTRACT: In recent years there has been intense interest in teachers' occupational stress in the educational community. The aim of the present study was to investigate the relationship between occupational stress and self-efficacy among primary school teachers working in mainstream and special education schools. The sample consisted of 501 teachers (412 women and 89 men) working in schools mainly in Athens, Greece. The Occupational Stress Scale for teachers and the Teachers' Sense of Efficacy Scale were administered to the teachers. The findings showed that the specific stress factors for teachers included government and school administration's favouritism, time pressure and pupils' character, pupils' improvement, resources and equipment, as well as support from parents and society. Moreover, mainstream school teachers reported higher levels of stress and higher levels of self-efficacy in comparison to special educational needs teachers. Individual variables were also shown to have an effect of teachers' stress and self-efficacy.